Synthesis of sparse planar arrays in the whole field by compressed sensing. Issue 23 (1st November 2019) - Zhao, Dongdong; Chen, Peng; Hu, Yingtian; Liang, Ronghua; Wang, Haixia; Guo, Xinxin
Abstract : A method for designing sparse large planar arrays in whole field with a minimum number of elements is proposed in this Letter. The method is developed by compressed sensing algorithms and a new composite beam pattern covering both far‐ and near‐field information. The experimental results demonstrate that the sparse planar array achieves a 95.3% element thinning compared to the fully sampled planar array and the side lobe peaks in near‐field conditions are at least 3.4 dB lower than those in previous studies.